2022
DOI: 10.1101/2022.04.07.487474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer-associated fibroblast-derived ROR2 induces WNT/PCP activation and polarized migration in receiving gastric cancer cells

Abstract: Bone marrow-derived mesenchymal stem cells and cancer-associated fibroblasts in the tumor-stromal environment have been linked to cancer progression in many studies. These fibroblasts provide signaling factors to the tumor cells that promote proliferation, survival, invasion, and metastasis. One signaling pathway influencing tumor cell behavior is the WNT/Planar Cell Polarity (PCP) signaling in gastric cancer. Here, we show that the gastric tumor cell line, AGS, can respond to the PCP ligand WNT5A, however, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Furthermore, in human glioma cells EGFRvIII is distributed by extracellular vesicle-based transfer to activate other membrane-associated oncogenic tyrosine kinases such as HER2, KIT and MET 57 . Our group recently demonstrated that ROR2 and WNT5A are significantly correlated on cytonemes of human cancer-associated fibroblasts; in the same study, ROR2 was identified in the cytoneme-receiving gastric tumour cells influencing migration of gastric cancer cells 58 , suggesting a conserved signalling role in vertebrate embryogenesis and disease.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, in human glioma cells EGFRvIII is distributed by extracellular vesicle-based transfer to activate other membrane-associated oncogenic tyrosine kinases such as HER2, KIT and MET 57 . Our group recently demonstrated that ROR2 and WNT5A are significantly correlated on cytonemes of human cancer-associated fibroblasts; in the same study, ROR2 was identified in the cytoneme-receiving gastric tumour cells influencing migration of gastric cancer cells 58 , suggesting a conserved signalling role in vertebrate embryogenesis and disease.…”
Section: Discussionmentioning
confidence: 79%
“…In a parallel study by our group, we provide further evidence that in gastric cancer, ROR2, and the relevant ligand WNT5A are significantly correlated on cytoneme in human cancer-associated fibroblasts. We also identify these clusters in the cytoneme-receiving gastric tumor cells (Rogers et al, 2022). Moreover, cytoneme-dependent spreading of WNT5A/ROR2 complexes is critical for polarization and directed migration of the gastric cancer cells.…”
Section: Discussionmentioning
confidence: 91%